Optimizing Hemp Fiber Production for High Performance Composite Applications - Musio, Salvatore; Müssig, Jörg; Amaducci, Stefano (Frontiers in Plant Science, 2018)
Hemp is a sustainable and environmental friendly crop that can provide valuable raw materials to a large number of industrial applications. Traditionally harvested at full flowering for textile destinations, nowadays hemp is mainly harvested at seed maturity for dual-purpose applications and has a great potential as multipurpose crop. However, the European hemp fibre market is stagnating if compared to the growing market of hemp seeds and phytocannabinoids. To support a sustainable growth of the hemp fibre market, agronomic techniques as well as genotypes and post-harvest processing should be optimised to preserve fibre quality during grain ripening, enabling industrial processing and maintaining, or even increasing, actual fibre applications and improving high-added value applications. In this paper, the effect of genotypes, harvest times, retting methods and processing on the yield and quality of long hemp for wet spun yarns was investigated. Conventional green-stem varieties were compared with yellow-stem ones on two harvesting times: at full flower and seed maturity. Scutching was performed on un-retted stems and dew-retted stems, the un-retted scutched fibre bundles were then bio-degummed before hackling. Both scutching and hackling was performed on flax machines. Quality of hackled hemp, with particular reference to its suitability for high performance composites production, was assessed. The results of fibre extraction indicate that yellow-stem varieties are characterized by higher scutching efficiency than green-stem varieties. Composites strength at breaking point, measured on specimens produced with the Impregnated Fibre Bundle Test, was lower with hemp obtained from stems harvested at seed maturity than at full flowering. On average, back-calculated fibre properties, from hackled hemp-epoxy composites, proved the suitability of long hemp fibre bundles for high performance composites applications, having properties comparable to those of high quality long flax.